Impact of financial distress on the dividend policy of banks in India - Anureet Virk Sidhu; Pooja Jain; Satyendra Pratap Singh; Jagjeevan Kanoujiya; Aashi Rawal; Shailesh Rastogi; Venkata Mrudula Bhimavarapu (Journal of Risk and Financial Management, 2023)
The present study primarily examines the impact of financial distress (FD) on the dividend policy of 33 banks working in the Indian economy from 2010 to 2019. In addition, we further explore the association between financial distress and dividend policy under the influence of shareholder activism (SHA). Using the static panel data regression technique, it is revealed that financial distress is non-linearly associated with the dividend policy of banks in an inverted U-shape. In the initial phase of a distressing situation, banks tend to have a liberal dividend policy. However, after reaching the pressure point, the banks start to squeeze dividend distribution to the stakeholders. Furthermore, the significant impact of shareholder activism has been found in the association between financial distress and the dividend payout policy of banks. From the policy perspective, the study will provide the policymakers with a clear all-round perspective of distressing situations, as the current research involves exploring the impact of distress on the dividend policy that will help the experts in basically understanding the adverse effect of financial distress and the repercussions, respectively, on the earning of the shareholders.
Keywords: 650; banks; dividend; financial distress; India; panel data regression